Pengembangan Modul Layanan Informasi untuk Mengembangkan Kontrol Diri dalam Penggunaan Smartphone - Rambe, Syarifah Ainy; Mudjiran, Mudjiran; Marjohan, Marjohan (Universitas Negeri Padang, 2017)
Self control is very important in daily life because self control was not developed well yet that can makeÂ individual has potential to make negative thing so individual must be developed their self control in smartphone usage. The purposes in this research are 1) To produce information service module to developed self control in smartphone usageÂ that is materially and appearance. 2) To describe the module level of exposure by the BK teacher/counselor. This research used development research by following ADDIE (Analysis, Design, Development, Implementation and Evaluation) as method of this research. Subject of trialÂ in this research consist of 3 experts to test the feasibility and 5 BK teacher/ counselor to test the module usage. The research was conducted by testing a product of research and Focus Group Discussion (FGD). The result of this research showing that 1) Information module service to developed self-control in smartphone usage valued worthy in terms of material and appearance. 2) Module usage is in the highest level. So the prototype of an information service to developed self control in smartphone usage module can be utilized by BK teacher/counselor to help the students in developing self-control in smartphone usage.